THE BUILDING OF MARKETING PERFORMANCE BASED ON PRODUCT INNOVATION AND COMPETITIVE ADVANTAGES OF BATIK CRAFTS - Siti Fatonah; I Gusti Putu Diva Awatara (Universitas Muhammadiyah Semarang, 2018)
In the business world, competition is getting tighter. As the complexities and dynamics of thebusiness environment intensify, companies begin to push to further strengthen their strategicbases with concepts such as customer focused or oriented cultures. community. There areseveral factors that can affect employee performance. The purpose of this study is to test theperformance of marketing-based product innovation and competitive advantage. This research is survey. Data collection techniques conducted in this study usingquestionnaires. The data used is the primary data from respondents' answers. Samplingtechnique in this research using random sampling, in this research the sample used is 110batik industry. Methods of data analysis were tested with Structural Equation Modelingthrough Smart PLS (Partial Least Square) program. The result of the research shows that the environmental uncertainty have positive andsignificant influence to the product innovation, the intensity of R & D influences positive andsignificant influence to product innovation, product innovation has positive and significantinfluence to marketing performance, product orientation has positive and significant influenceto competitive advantage, influential positive and significant influence to competitiveadvantage, competitive advantage have positive and significant influence to marketingperformanceKeywords: environmental uncertainty, product innovation, R & D intensity, product orientation, competitive advantage, customer orientation, marketing performance.